Spotlight - The 13th Annual Mineral Processing Symposium - Gordon?s Bay, 3-5 August, 1994 - F. W. Petersen (The Southern African Institute of Mining and Metallurgy, 1994)
For the past thirteen years, the Universities of Cape Town and Stellenbosch have hosted an annual symposium to discuss topics relevant to mineral processing. Since 1987, this Symposium has been held under the auspices of the Western Cape Branch of the South African Institute of Mining and Metallurgy, and has become one of the main events on the national conference calendar. In 1989 and 1993, the symposia took the shape of international conferences. This year the 13th Annual Mineral Processing Symposium was organized by the two universities, the Cape Technikon, and the local branch of the South African Institute of Mining and Metallurgy, and was held at the Van Riebeeck Hotel in Gordon's Bay.